Efecto del pH sobre el perfil de péptidos potencialmente bioactivos producidos por Lactococcus lactis subsp. cremoris NCFB 712 - Figueroa Hernández, Claudia Yuritzi (Universidad Autónoma Metropolitana, 2012)
Milk protein derived peptides could exert physiology functions in human body, mainly antihypertensive activity by the inhibition of the Angiotensin Converting Enzyme (ACE). These peptides can be liberated by proteolytic microorganism during fermentation. In this work the effect of pH on the production of bioactive peptides during milk fermentation by Lactococcus lactis subsp. cremoris NCFB 712 was studied. The proteolytic activity (measured by TNBS) was higher in the fermentations with pH control (pH 6.2) than in the fermentations without control even it was not observed higher concentrations of peptides of less than 10 k Da compared to the fermentation without pH control. The peptide profiles in both fermentations showed differences since the eighth hour of fermentation, when the pH value of the fermentations began to show statistical significance. It is thought that these differences in peptide profiles are mainly due to effect of pH on both proteolytic activity and specificity of cell wall proteinase type 1 (CEP-I), that is the type of enzyme that has the microorganism used for supported their growth in milk. The fermentation without pH control has a higher percent of ACE-inhibitory activity and a lower IC50 value, therefore has higher ACE- inhibitory potency. However when carry out the simulation of gastrointestinal digestion (with pepsin and trypsin) the ACE-inhibitory activity of this hydrolysates decreased in 14%, while the fermentations with pH control keep their ACEinhibitory activity after an enzymatic digestion. The peptide fraction with higher ACE-inhibitory activity has a having a molecular weight determinate by exclusion HPLC close to 0.58 kDa which is very important because the majority of the peptides with ACE-inhibitory activity have molecular weights less than 1 kDa. This fraction was re-fractionated by RP- HPLC finding 4 sub-fractions; three of them showed high ACE- inhibitory activity and one a higher concentration than the others. With respect to the binding of minerals was observed that the pH-controlled fermentation has the ability to bind iron and calcium while the samples from the fermentation without pH control only have the ability to bind calcium in a lower concentration than in fermentations with pH control.; Los péptidos derivados de las proteínas de la leche pueden ejercer funciones fisiológicas en el cuerpo humano, una de las actividades más estudiadas es la actividad antihipertensiva, la cual se ejerce por medio de la inhibición de la enzima convertidora de Angiotensina (ACE). Estos péptidos pueden ser liberados a partir de las proteínas precursoras durante la fermentación con microorganismos proteolíticos. En este trabajo se estudió el efecto del pH en la producción de péptidos bioactivos durante la fermentación de la leche con Lactococcus lactis subsp. cremoris NCFB 712. La actividad proteolítica (medida por TNBS) fue mayor en las fermentaciones con control de pH (pH 6.2) aunque no se observó una mayor concentración de péptidos menores a 10 k Da con respecto a la fermentación sin control de pH. Los perfiles peptídicos en las fermentaciones con y sin control de pH, muestran diferencias a partir de la octava hora de fermentación, por lo que se piensa que esta diferencia en los perfiles peptídicos se debe principalmente al efecto de pH sobre la especificidad y la actividad proteolítica de la proteinasa ligada a pared celular tipo 1 (CEP-I), de Lactococcus lactis subsp. cremoris NCFB 712 que le permite crecer en la leche. La fermentación sin control de pH mostró tener un mayor porcentaje de actividad inhibidora de la ACE y por lo tanto un valor menor de IC50 y una mayor potencia inhibidora de la ACE. Sin embargo al llevar a cabo la simulación del proceso de digestión gastrointestinal (con pepsina y tripsina) la actividad inhibidora de la ACE de esta fermentación presentó una disminución de 14% mientras que las muestras de la fermentación con control de pH mantuvieron su actividad inhibidora de la ACE después de la digestión. La fracción peptídica con mayor actividad inhibidora de la ACE tuvo un peso molecular de 0.58 kDa (determinada por HPLC), lo cual coincide con lo reportado previamente, ya que la mayoría de los péptidos inhibidores de la ACE tienen pesos moleculares menores a un 1 kDa. Esta fracción se purificó por medio de cromatografía en fase reversa (RP-HPLC), donde se encontraron tres fracciones peptídicas con una alta actividad inhibidora de la ACE. Con respecto a la fijación de minerales, se observó que los péptidos de la fermentación con control de pH presentaron una mayor habilidad para fijar el calcio y el hierro que los péptidos obtenidos en la fermentación sin control de pH.